Real-time, dynamic monitoring of selectively driven ion-concentration polarization. (10th September 2022) - Flavin, Matthew T.; Lissandrello, Charles A.; Han, Jongyoon
Abstract: Selective ion extraction is a vital element of many resource recovery systems. Carrier-based membranes offer the ability to remove specific, targeted ions from brine and waste streams, but these materials have delivered inconsistent outcomes in their active transport applications. To study non-ideal behaviors of target-ion selective membranes, we introduce a direct, real-time system for selectively measuring concentrations within electro-membrane boundary layers. In a carrier-based membrane system, we applied our method to monitor adverse, current-limiting behaviors. During its operation, we detected loss of transport selectivity and counter-ion discharge. It provided sufficient evidence to identify the mechanism underlying these adverse, over-limiting effects—the internal concentration polarization of free-carrier. Our method may raise new prospects for direct experimental characterization of nonlinear transport phenomena in electro-membrane systems.